Correlation between score for allergic rhinitis and quality of life in chronic rhinitis patients - Asti Widuri; Tri Wahyuliati; Winda Retno Ningrum (Oto Rhino Laryngologica Indonesiana, 2021)
ABSTRACTBackground: Allergic rhinitis is a chronic inflammatory condition of the nasal mucosa that occurs as an Imunoglobulin E (IgE) mediated reaction after provocation of allergen. The prevalence of rhinitis in Indonesia reaches 12.4% and still rising. Chronic rhinitis can affect the quality of life, especially daily activities and sleep disturbances. Purpose: This study aimed to determine the correlation between the Score for Allergic Rhinitis (SFAR) and the patient’s quality of life (QOL) using allergic rhinitis mobile phone application. Method: This was an observational analytic research using cross sectional method. The number of samples was 46 with predetermined inclusion and exclusion criteria. The research instrument used was a mobile phone application of SFAR and for quality of life was Visual Analog Scales (VAS) questionnaire. Data analysis was using Shapiro-Wilk for normality test and contingency coefficient test to determine the correlation between variables. Result: The result showed that there was a significant correlation between the Score for Allergic Rhinitis and the quality of life in chronic rhinitis sufferers (p = 0.000). The correlation had uni-direction and moderate strength (r = 0.567). There were 52.17% respondents who stated that rhinitis complaints would be reduced after using nasal drugs/sprays. And for the VAS parameter, the highest number given was 0 in 45.65% respondents, which meant that they did not feel any discomfort. Conclusion: There was a significant correlation between SFAR and quality of life AR sufferers with moderate strength and uni-direction.Keywords: Score for Allergic Rhinitis, quality of life, rhinitis, mobile applicationABSTRAKLatar belakang: Rinitis alergi adalah kondisi inflamasi kronis pada mukosa hidung sebagai reaksi yang dimediasi Imunoglobulin E (IgE) setelah provokasi alergen. Prevalensi rinitis di Indonesia mencapai 12,4 % dan akan terus meningkat. Rinitis kronik dapat memengaruhi kualitas hidup terutama aktivitas sehari-hari dan gangguan tidur. Tujuan: Penelitian ini bertujuan untuk mengetahui korelasi Score for Allergic Rhinitis (SFAR) dengan kualitas hidup penderita menggunakan aplikasi rinitis alergi pada telepon genggam. Metode: Penelitian ini berupa analitik observasional dengan desain cross sectional. Sampel yang digunakan sebanyak 46 responden dengan kriteria inklusi dan eksklusi yang sudah ditentukan. Instrumen penelitian menggunakan aplikasi telepon genggam berisi kuisioner SFAR dan kualitas hidup dengan Visual Analog Scales (VAS). Analisis data menggunakan Shapiro-Wilk untuk uji normalitas dan uji koefisien kontingensi untuk mengetahui korelasi antar variabel. Hasil: Didapatkan hasil berupa hubungan korelasi yang bermakna antara skor SFAR dengan kualitas hidup penderita rinitis kronik (p=0,000). Hubungan korelasi tersebut memiliki satu arah dan kekuatan yang sedang (r=0,567). Diperoleh pernyataan dari 52,17% responden bahwa keluhan rinitis akan berkurang setelah minum obat/menggunakan semprot hidung. Untuk parameter VAS didapatkan hasil bahwa angka terbanyak yang diberikan adalah 0 pada 45,65% responden, yang berarti tidak merasakan ketidaknyamanan. Kesimpulan: Terdapat korelasi bermakna antara SFAR dan kualitas hidup penderita AR dengan kekuatan hubungan sedang dan satu arah.Kata kunci: Score for Allergic Rhinitis, kualitas hidup, rinitis, aplikasi telepon genggam